Career Women Viewed from Qur'an Feminism - Rus miyati (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Thinking about women is no longer just identified with household and kitchen matters, but thinking about women is directly related to the outside world, namely as a career woman. The focus of this research is more on the Qur'anic concept of feminism and how it should be a career woman in an understanding that is conveyed in the Qur'an. This study uses descriptive methods that are carried out through data collection in the field, which provides an overview of career women in the view of Islam. This research approach uses a qualitative approach. The research data is in the form of quotes, words, phrases, and story sentences. The source of data in this study is the observation of several career women in the Sidoarjo city area. The results of this study indicate that women are very respectable in Islam. A number of Qur'anic verses support this conclusion. Even Qur'anic respect for women transcends the concept of Western feminism. Keywords: Thinking, Qur'anic Feminism, Women, Career, Descriptive Qualitative.